PRODUTIVIDADE DE FEIJÃO-CAUPI CULTIVADOS NA REGIÃO DO ECÓTONO CERRADO/PANTANAL - CORRÊA, Gabriela Guedes; SANTOS, Carla Medianeira Giroletta; SILVA, Jeferson Antonio dos Santos; CAPRISTO, Denise Prevedel; RODRIGUES, Taiciara Cleto; CORREA, Jonas de Sousa (ANAIS DO ENIC, 2020)
-